Evaluation of Strategic Positioning and Change Management through SWOT Analysis at XYZ Elementary School - Isnawati Isnawati; Hapzi Ali (Dinasti Publisher, 2026)
This study was motivated by the rapid changes in education policy, which require elementary schools to be flexible in maintaining the quality of their services. The primary focus of this study is to analyze the roles of Strategic Positioning and Change Management in building organizational adaptability at XYZ Elementary School. Using Dynamic Capabilities Theory as its theoretical foundation, this study explores the school’s ability to sense shifts in a complex external environment. The research method used is qualitative with an in-depth case study approach, in which data is collected through interviews and observations of school stakeholders to comprehensively understand the process of strategy internalization and policy operationalization mechanisms. The results of the SWOT analysis indicate that the success of the school’s vision and mission depends heavily on the leadership’s ability to reconfigure organizational resources in order to address bureaucratic and technical obstacles. The findings reveal that synergy between strategic positioning and change management agility can significantly minimize internal resistance during the transformation process. This study concludes that adaptability is a strategic dynamic capability that determines the sustainability of quality and the school’s competitiveness amid the uncertainty of the educational environment. The practical implications of this study emphasize the importance of strengthening strategic literacy for school administrators to convert external challenges into opportunities for sustainable institutional innovation.